2014
DOI: 10.1007/s00438-014-0870-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptome analysis of Arabidopsis response to sulfur dioxide fumigation

Abstract: Sulfur dioxide (SO2) supplies the basic sulfur element to promote plant growth, yet at the same time it is a harmful air pollutant. Currently, the mechanisms of plant adaptation to SO2 stress are largely unknown. Pathways of SO2 metabolism, a range of networks of interacting regulatory signals and defense mechanisms triggered in resistance to SO2 stress, have not yet been clarified. We performed transcriptome analysis of Arabidopsis plants fumigated with 30 mg m(-3) SO2 for 72 h and untreated controls using mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…Transcriptome-wide analysis of A. thaliana plants fumigated with SO 2 revealed that large amounts of sulfite were involved in sulfur assimilatory pathways directly and uncoupled from sulfite oxidative pathways. Furthermore, transcripts associated with biotic stress, as well as with reactive oxygen species generating and scavenging pathways were markedly up-regulated [219]. Interestingly, pre-treatment of A. thaliana plants with SO 2 also resulted in significantly enhanced resistance to infection with the necrotrophic fungus B. cinerea.…”
Section: Reactive Sulfur Species (Rss)mentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptome-wide analysis of A. thaliana plants fumigated with SO 2 revealed that large amounts of sulfite were involved in sulfur assimilatory pathways directly and uncoupled from sulfite oxidative pathways. Furthermore, transcripts associated with biotic stress, as well as with reactive oxygen species generating and scavenging pathways were markedly up-regulated [219]. Interestingly, pre-treatment of A. thaliana plants with SO 2 also resulted in significantly enhanced resistance to infection with the necrotrophic fungus B. cinerea.…”
Section: Reactive Sulfur Species (Rss)mentioning
confidence: 99%
“…Besides H 2 S, the metabolism of another RSS, the sulfite anion has recently been also associated with plant disease resistance as a possible signal molecule [200,218,219]. Endogenous sulfite (SO 3 2− ) levels in A. thaliana and tomato were determined by Brychkova [220].…”
Section: Reactive Sulfur Species (Rss)mentioning
confidence: 99%
“…The explanation is that plants could become injured in a SO 2 concentration range from 131 to 1,310 μg m −3 ; plants, however, can rapidly assimilate SO 2 and H 2 S into reduced sulfur pools such as cysteine and sulfates as illustrated in Figure 1 . A recent transcriptome analysis of Arabidopsis responses to SO 2 showed that plant adaptation to SO 2 evokes a comprehensive reprogramming of metabolic pathways including NO and reactive oxygen species (ROS) signaling molecules, and also plant defense response pathways (Zhao and Yi, 2014 ). The importance of this study revealed that plant responses to SO 2 stress is at the transcription level with initial activation of cross tolerance and followed by sulfur assimilation pathways.…”
Section: Roles Of Leaves and Phyllosphere Microbes In Air Remediationmentioning
confidence: 99%
“…Transcriptome analysis of Arabidopsis leaves and roots treated with 1 mM GSNO for 3 h revealed differential expression of 3263 genes involved in many physiological processes, including biotic and abiotic stress tolerance (Begara-Morales et al, 2014 ). Similarly, other Arabidopsis transcriptome analyses have been performed to measure responses to various stimuli such as oxidative stress (Desikan et al, 2001 ), nitrogen limitation (Peng et al, 2007 ), phosphate starvation (Woo et al, 2012 ), nanoparticles (García-Sánchez et al, 2015 ), cold stress (Zou and Yu, 2010 ), salt stress and ABA treatment (Matsui et al, 2008 ), auxin (Paponov et al, 2008 ), insect attack (Kempema et al, 2007 ; Ehlting et al, 2008 ), metal toxicity (Weber et al, 2006 ), and fumigation with sulfur (Zhao and Yi, 2014 ). Similar transcriptome analyses in Arabidopsis have also been performed at a more basal level to understand physiological functions such as plant defense (Eulgem, 2005 ; Ditt et al, 2006 ; Postnikova and Nemchinov, 2012 ; Weeda et al, 2014 ), development (Gandotra et al, 2013 ), and embryogenesis (Li et al, 2007 ), whereas other studies have investigated transcriptomics in relation to various specific tissues or organs, including pollen (Grennan, 2007 ; Zou and Yu, 2010 ), anthers (Feng et al, 2012 ), floral parts (Zhang et al, 2015 ), root hairs (Jones et al, 2006 ), guard cells (Wang et al, 2011 ), and leaves (Gandotra et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%